MEMBENTUK KARAKTER BANGSA MELALUI PENDIDIKAN KEWARGANEGARAAN - Annisa Arnun (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This research intends to shape the national character through Pancasila education, this is done because the current national character, especially millennials, is increasingly being eroded and eroded by technological developments and the times, so that the national character, especially millennials, is very far from what is contained in the 1945 Constitution, so the presence of civics education is needed in order to shape the character of the nation in accordance with the 1945 Constitution. This research uses literature studies or qualitative research methods with literature studies, in which this study intends to present research results with descriptions or descriptions to answer research problems, and the results of the research show that citizenship education is needed not only in the world of education but also in everyday life in order to form a national character that is in line with the 1945 Constitution.